184k views
0 votes
(HELP PLEASE!) Which expression is equivalent to? Assume.

(HELP PLEASE!) Which expression is equivalent to? Assume.-example-1
User JohanTG
by
5.2k points

1 Answer

3 votes

Answer:

Option 1

Explanation:

Given expression is:


((2mn)^(4))/(6m^(-3)n^(-2)) \\=(2^(4)m^(4)n^(4))/(6m^(-3)n^(-2))\\=(16m^(4)n^(4))/(6m^(-3)n^(-2))\\=(8*2*m^(4)*n^(4))/(2*3*m^(-3)*n^(-2)) \\=(8*m^(4+3)n^(4+2))/(3)\\=(8m^(7)n^(6))/(3)

So option 1 is the correct answer ..

User Lachanda
by
5.7k points